2012
DOI: 10.1111/j.1365-2702.2012.04091.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of body fluid status in hemodialysis patients using the body composition monitor measurement technique

Abstract: We propose that experienced HD nursing staff be trained in the use of the BCM or other simple bioimpedance machines to help monitor patient overhydration and approximate dry weight in consultation with the nephrologists responsible for the care of these patients so as to obviate excessive residual overhydration between nephrology reviews.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…On univariate analysis, the change in OH index correlated positively with the change in ECW, and negatively with the change in ICW and TBW. This is in agreement with a previous study that reported the majority of weight loss recorded was due to a reduction in ECW, with a much smaller change in ICW . The BCM differs from many other BIA devices in that it uses a different body composition model, dividing the body into three compartments, and then uses an algorithm to predict OH compared to that of a healthy age‐matched, sex‐matched and weight‐matched individual, so that BCM measurements of OH pre‐dialysis have been be used to adjust ultrafiltration to aid achieving target weight .…”
Section: Discussionsupporting
confidence: 89%
“…On univariate analysis, the change in OH index correlated positively with the change in ECW, and negatively with the change in ICW and TBW. This is in agreement with a previous study that reported the majority of weight loss recorded was due to a reduction in ECW, with a much smaller change in ICW . The BCM differs from many other BIA devices in that it uses a different body composition model, dividing the body into three compartments, and then uses an algorithm to predict OH compared to that of a healthy age‐matched, sex‐matched and weight‐matched individual, so that BCM measurements of OH pre‐dialysis have been be used to adjust ultrafiltration to aid achieving target weight .…”
Section: Discussionsupporting
confidence: 89%
“…Our results, demonstrate that the majority of change in OH is due to a change in ECW, which supports a previous report of using BIS and a 3-compartmental body composition model [19,20]. As such, pre-dialysis measurements of OH have been used to aid clinical decision making in terms of the amount of ultrafiltration required to return patients to a normo-volaemic state [21].…”
Section: Discussionsupporting
confidence: 72%
“…The PNC focused on liquid intake showed a positive impact on fluid status of overhydrated patients as the mean value declined over the follow‐up period. Nevertheless, the prevalence of severe OH within participants increased during the study period (P = 0.283), suggesting that some patients who were not severely overhydrated (OH/ECW > 15%) at the beginning of the study, became so after the intervention, probably because in these cases, fluid intake was not the focus of the nutritional intervention or perhaps because of the need of adjusting patients DW …”
Section: Discussionmentioning
confidence: 99%